Saudi Vision 2030: Opportunities and Challenges of Thai Labor Market - Akarapisit, Arisara (Siam University Journal of Business Administration, 2022)
The historical country reform in line with Saudi Vision 2030 could be one reason to let Saudi Arabia have fully restored diplomatic ties with Thailand after the dispute over three decades. With the ultimate ambition to reduce its dependency on oil revenues and enhance economic diversification, Saudi Arabia needs millions of migrant workers to fulfill the development projects. The official visit on January 25-26, 2022 to Saudi Arabia by Prime Minister Prayut Chan-o-cha at the invitation of the Saudi crown prince creates opportunities for bilateral cooperation and development in various sectors between the two kingdoms, and one of those is labor cooperation arrangements. The restoration of working ties between the countries shows a promising opportunity to bring back Thai workers to Saudi Arabia, whereas there might be several challenges to overcome. Therefore, how far the success of exporting Thai workers to Saudi Arabia depends on the attempts both at the government and individual levels.